Structures, and Thermophysical Properties Characterizations of (La1-xHox)3NbO7 Solid Solutions as Thermal Barrier Coatings - Chen, Lin; Wang, Yitao; Zheng, Qi; Feng, Jing (Frontiers in Materials, 2021)
A sequence of (La1-xHox)3NbO7 solid solutions were fabricated in this work, which were studied as candidate thermal insulation materials. The lattices were identified via XRD, when SEM and EDS were used to characterize the microstructures and element distributions. The results showed that the highest modulus, hardness and toughness of (La1-xHox)3NbO7 were 196 GPa, 9.2 GPa and 1.6 MPa·m1/2, respectively; and they accorded with the mechanical properties requirements. Also, low thermal conductivity (1.06 W·m-1·K-1) and high thermal expansion coefficients (TECs: 11.3×10-6 K-1) were simultaneously realized in (La3/6Ho3/6)3NbO7, at high temperatures. No phase transition was detected up to 1200 ˚C, which proved their good lattice stability. The intense an-harmonic lattice vibrations may contribute to the outstanding thermal properties of (La1-xHox)3NbO7 ceramics. The suitable modulus, high hardness, low thermal conductivity and high TECs of (La1-xHox)3NbO7 solid solutions proclaimed that they were exceptional thermal insulation ceramics.